Target product profile development based on market segment status - Gitonga, Agnes; Donovan, Jason; Muungani, Dean; Coaldrake, Peter (CGIAR Initiative on Market Intelligence, 2024)
The article discusses the development of Target Product Profiles (TPPs) based on market segment status, focusing on seed product market segments (SPMSs) for crops served by CGIAR breeding programs. It outlines how over 600 market segments are identified using eight criteria, and how these segments guide discussions between market intelligence researchers and breeding teams to ensure that seed products meet the required traits for farmers. The Target Product Profile serves as a blueprint for designing seed products that satisfy the needs of farmers, processors, and consumers, ensuring that essential traits meet the minimum acceptable standards for each segment.